The transcription factor dFOXO controls the expression of insulin pathway genes and lipids content under heat stress in Drosophila melanogaster - M. A. Eremina; P. N. Menshanov; O. D. Shishkina; N. E. Gruntenko (Вавиловский журнал генетики и селекции)
The insulin/insulin-like growth factor signaling (IIS) pathway is one of the key elements in an organism’s response to unfavourable conditions. The deep homology of this pathway and its evolutionary conservative role in controlling the carbohydrate and lipid metabolism make it possible to use Drosophila melanogaster for studying its functioning. To identify the properties of interaction of two key IIS pathway components under heat stress in D. melanogaster (the forkhead box O transcription factor (dFOXO) and insulin-like peptide 6 (DILP6), which intermediates the dFOXO signal sent from the fat body to the insulin-producing cells of the brain where DILPs1–5 are synthesized), we analysed the expression of the genes dilp6, dfoxo and insulin-like receptor gene (dInR) in females of strains carrying the hypomorphic mutation dilp641 and hypofunctional mutation foxoBG01018. We found that neither mutation influenced dfoxo expression and its uprise under short-term heat stress, but both of them disrupted the stress response of the dilp6 and dInR genes. To reveal the role of identified disruptions in metabolism control and feeding behaviour, we analysed the effect of the dilp641 and foxoBG01018 mutations on total lipids content and capillary feeding intensity in imago under normal conditions and under short-term heat stress. Both mutations caused an increase in these parameters under normal conditions and prevented decrease in total lipids content following heat stress observed in the control strain. In mutants, feeding intensity was increased under normal conditions; and decreased following short-term heat stress in all studied strains for the first 24 h of observation, and in dilp641 strain, for 48 h. Thus, we may conclude that dFOXO takes part in regulating the IIS pathway response to heat stress as well as the changes in lipids content caused by heat stress, and this regulation is mediated by DILP6. At the same time, the feeding behaviour of imago might be controlled by dFOXO and DILP6 under normal conditions, but not under heat stress.